Innovation of Digital Economy Cases from China - Zhang, Jianlin; Ying, Kezhen; Wang, Kanliang; Fan, Zhigang; Zhao, Ziyi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents a rich selection of 36 real-world cases on how organizations in China explore the new growth pattern, business model innovation, and digital transformation in digital era. The topic of cases varies from digital marketing and Internet brands, the growth of digital platforms, digital transformation and the industrial Internet of things, strategies for cross-border e-commerce companies, and business model innovation in digital era, etc. These cases stem from a diverse set of industry sectors, reporting on best practices and lessons learned. The book shows how organizations strive to find new ways to develop and create new paths to grow in a digital world and shares essential practical insights into digital economy. All cases are presented in a standardized structure in order to provide valuable insights and essential guidance for practitioners, scholars as well as general readers.
Introduction to Digital Economy In China: Innovation to Practice -- Chapter One: Internet Brands and Digital Marketing -- Chapter Two: The Emergence and Growth of Digital Platform -- Chapter Three: Industrial Internet of Things -- Chapter Four: Digital Service -- Chapter Five: Data-Driven Business Model Innovation -- Chapter Six: Cross-Border E-commerce.
Keywords: Electronic commerce; Technological innovations; E-Business.; e-Commerce and e-Business.; Economics of Innovation